2015
DOI: 10.1371/journal.pone.0117498
|View full text |Cite|
|
Sign up to set email alerts
|

Tempol Treatment Reduces Anxiety-Like Behaviors Induced by Multiple Anxiogenic Drugs in Rats

Abstract: We have published that pharmacological induction of oxidative stress (OS) causes anxiety-like behavior in rats. Using animal models, we also have established that psychological stress induces OS and leads to anxiety-like behaviors. All evidence points towards the causal role of OS in anxiety-like behaviors. To fully ascertain the role of OS in anxiety-like behaviors, it is reasonable to test whether the pro-anxiety effects of anxiogenic drugs caffeine or N-methyl-beta-carboline-3-carboxamide (FG-7142) can be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…This is in agreement with our previous studies in which we had reported antianxiety effect of GP in 3 separate rodent models [18,27,36]. Anxiety-like behaviors induced by L-buthionine-(S,R)-sulfoximine [18], single prolonged stress [27], and ovariectomization [28] were prevented with GP treatment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with our previous studies in which we had reported antianxiety effect of GP in 3 separate rodent models [18,27,36]. Anxiety-like behaviors induced by L-buthionine-(S,R)-sulfoximine [18], single prolonged stress [27], and ovariectomization [28] were prevented with GP treatment.…”
Section: Discussionsupporting
confidence: 92%
“…This is in tandem with our previous observations in which behavioral and cognitive impairments noted in other rodent models [3,27,28] were associated with elevated plasma corticosterone levels [3,27,28]. In addition to examining the protective role of GP using systemic evaluation of stress, we also examined the level of neuronal stress using a biochemical marker of neuronal activation, c-fos [34,36]. We focused on 3 regions of the brain, namely, the hippocampus, amygdala, and prefrontal cortex, areas implicated in anxiety, cognition, and Fig.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Caffeine alters LMA at low doses (10-30 mg/kg), and at higher doses (≥ 50 mg/kg), it exerts anxiogenic effects (Baldwin and File, 1989, Bhattacharya et al , 1997, Collins et al , 2010, Cook and Beardsley, 2003, El Yacoubi et al , 2000, Garrett and Holtzman, 1994, Halldner et al , 2004, Kaplan et al , 1992, Kuzmin et al , 2006, Patki et al , 2015, Solinas et al , 2002, Svenningsson et al , 1995, Zhang et al , 2011). Higher doses of caffeine alter CART peptide levels in the NAc (Cho et al , 2015).…”
Section: Discussionmentioning
confidence: 99%